2018
DOI: 10.1016/j.heliyon.2018.e00525
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical alterations in inflammatory reactive chondrocytes: evidence for intercellular network communication

Abstract: Chondrocytes are effectively involved in the pathophysiological processes of inflammation in joints. They form cellular processes in the superficial layer of the articular cartilage and form gap junction coupled syncytium to facilitate cell-to-cell communication. However, very little is known about their physiological cellular identity and communication. The aim with the present work is to evaluate the physiological behavior after stimulation with the inflammatory inducers interleukin-1β and lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…The ratio between the polymer form of the F-actin and the monomer form of the G-actin was increased [25]. Similar changes of the actin filament structure are observed in chondrocytes [36]. Different stimuli that cause inflammation result in endocytosis of junction proteins, which causes barrier dysfunction.…”
Section: Disorganization Of Actin Filamentsmentioning
confidence: 70%
See 1 more Smart Citation
“…The ratio between the polymer form of the F-actin and the monomer form of the G-actin was increased [25]. Similar changes of the actin filament structure are observed in chondrocytes [36]. Different stimuli that cause inflammation result in endocytosis of junction proteins, which causes barrier dysfunction.…”
Section: Disorganization Of Actin Filamentsmentioning
confidence: 70%
“…The importance of the effect is seen in the chondrocytes in joints, that are connected to each other via cell-to-cell interactions and form functional gap junctions that express Cx43 [32]. They can sustain the propagation of intercellular Ca 2+ waves in rabbits, humans, and equines [33,34] and form hemichannels that exchange signals within the extracellular space [35,36]. In the adult cartilage, chondrocytes exist as individual cells embedded in the extracellular matrix, and gap junctions are mainly expressed by the flattened chondrocytes facing the outer cartilage layer where intercellular communication occurs [37].…”
Section: Syncytium Coupled Cellsmentioning
confidence: 99%
“…The results clearly showed that OAC responded differently to 5-HT stimulation compared to HC with respect to intracellular Ca 2+ release. We have previously shown that healthy chondrocytes alter Ca 2+ -evoked signalling from single peaks to oscillating waves when exposed to inflammatory mediators (IL-1β and LPS) ( Skiöldebrand et al., 2018 ). In the current study, OAC exhibited stronger intracellular Ca 2+ release than HC in response to 5-HT and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular Ca 2+ release was evoked by different signaling pathways stimulated by ATP and 5-HT. These cells also express Cx43 and TLR4 [30].…”
Section: Gap Junction-coupled Cellsmentioning
confidence: 99%
“…TLR4 is most likely present on all cells involved in immune function [26], including gap junctioncoupled cells. Examples of these cells include chondrocytes [30], cardiac fibroblasts [31], keratinocytes [32], and tenocytes [33]. TLRs are involved in the pathogenesis of autoimmune disease, chronic inflammatory and infectious diseases, leading to overproduction of autoantibodies [34].…”
Section: Toll-like Receptorsmentioning
confidence: 99%